Equity Term Structures without Dividend Strips Data - GIGLIO, STEFANO; KELLY, BRYAN; KOZAK, SERHIY (Journal of Finance, 2024)
ABSTRACT We use a large cross section of equity returns to estimate a rich affine model of equity prices, dividends, returns, and their dynamics. Our model prices dividend strips of the market and equity portfolios without using strips data in the estimation. Yet model‐implied equity yields closely match yields on traded strips. Our model extends equity term‐structure data over time (to the 1970s) and across maturities, and generates term structures for various equity portfolios. The novel cross section of term structures from our model covers 45 years and includes several recessions, providing a novel set of empirical moments to discipline asset pricing models.